Makna Ngeteh di Kalangan Remaja Akhir Pengguna Media Sosial Twitter - Utari, Setya Bella; Purnama, Dadang Hikmah (Master Program in Sociology, Faculty of Social and Political Sciences, Universitas Sriwijay, 2024)
The study aims to explore the meaning of @AreaJulid's late adolescent followers in social media groupings on Twitter through the phenomenological approach of Alfred Schutz. The research method used in this study is qualitative descriptive. Data collection techniques are carried out by observing participants on individual social media and Twitter, conducting in-depth interviews, and conducting documentation. The results of the research showed the significance of ngeteh among late adolescents who followed @AreaJulid's Twitter social media account, not apart from the because motive and in order motive that was acquired based on the experiences of late adolescents in ngeteh, thus forming awareness to be followers of ngeteh. Different experiences, from the usage routine to the content consumed, produce different meanings for each late adolescent, such as the desire to remain relevant, entertainment, and social control.